How do serum cytokine levels change in myocarditis and inflammatory dilated cardiomyopathy relative to healthy individuals? A protocol for a systematic review and meta-analysis - Romuald Wojnicz; Piotr Lewandowski; Maciej Baron; Marcin A Rojek; Marcin Goławski; Karol Krystek; Magdalena Żegleń; Pascal Zytkiewicz; Jakub Kancerek; Klaudia Gabriela Lis; Jakub Warecki; Jakub Kufel; et al. (BMJ Open)
Introduction Myocarditis is an inflammatory heart disease resulting from infections, toxic exposures or autoimmune reactions. Irrespective of the factors responsible for this disease, cytokines play an important role in regulating the immunological response involved in its development and progression. Accordingly, this protocol aims to conduct a systematic review and meta-analysis summarising previous research on serum and plasma levels of cytokines in patients with myocarditis and inflammatory dilated cardiomyopathy.Methods and analysis Four scientific databases: PubMed, Embase, Scopus and Web of Science, will be searched. The estimated date of the search will be 30 March 2024. Each stage of the review, including the study selection, data extraction, risk of bias and quality of evidence assessments, will be performed in duplicate. Studies meeting the following criteria will be eligible for inclusion: (1) studies involving ‘myocarditis’ or ‘inflammatory dilated cardiomyopathy’ and (2) studies are required to report serum levels of any cytokine. Meta-analyses will be used to summarise serum levels of each cytokine if possible. Subgroup analysis will be stratified by age, sex, sample size, New York Heart Association scale, cardiac Troponin T, N-terminal prohormone of brain natriuretic peptide, C reactive protein, number of lymphocytes per mm2 in the endomyocardial biopsy.Ethics approval and dissemination This study does not require ethics approval. After completion, the results will be published in a peer-reviewed paper. Data generated during the study will be published in an open access repository.PROSPERO registration number CRD42024519625